Adaptation of the territorial organisation of agriculture in a peripheral region to the operations of agricultural holdings - Kira A. Morachevskaya; Elena A. Lyzhina; Alexander B. Sebentsov; Mikhail S. Karpenko (Baltic Region)
Agricultural holdings are often cited as the main beneficiaries, on the one hand, of organisational and structural changes in Russian agriculture during the post-Soviet period, and on the other, of the transformation of state policy in response to contemporary geopolitical challenges. This paper examines the adaptation of the territorial and sectoral structure of agriculture in a socioeconomically peripheral region in response to the expansion of agricultural holdings. This study draws on official statistical data, the SPARK database, resources from the VetIS Federal State Information System, the Unified Federal Information System on Agricultural Land, and the authors’ extensive field research. The study demonstrated that the operations of agricultural holdings can completely transform the agricultural profile of a non-Chernozem region with a declining population in terms of specialisation and organisational structure, leading to economic recovery in agriculture. The example of the Pskov region illustrates how the expansion of agroholding assets is swiftly extending into peripheral areas with abundant land and low rural population density. The interviews confirmed that livestock agricultural holdings, primarily those specialising in pork production, benefit from the social desertification of rural areas. This is accompanied by a further weakening of rural community economies, as livestock and poultry have completely disappeared from private and subsistence farms. The new pork production specialisation in the Pskov region has, as expected, led to other changes in agriculture, including an increase in grain farming. While production volumes have risen, new territorial centres have not emerged.